Thinking about care from spatial continuity. Contributions of geography and feminist urbanism (Revista Rupturas, 2024)
This article takes the contributions of feminist perspectives in geography and urbanism as principal axes to explore how caretaking in everyday life challenges the public-private dichotomy of space. Statistical data demonstrates how the exercise of caretaking has a significant impact on the ways in which people make use of time and space. A reflection is offered that signals the urgency of subverting the established order to open the possibility for other space-time configurations that can sustain the dignity and diversity of life, as well as justice and legal equality.
Keywords: care; public-private space; daily life; sustainability of life